Global governance after the financial crisis: A new multilateralism or the last gasp of the great powers? - Ngaire Woods (University of Oxford, Global Economic Governance Programme (GEG), 2009)
In the wake of the global financial crisis, three G20 Summits have reinvigorated global cooperation, thrusting the International Monetary Fund centre-stage with approximately 1trillion of resources. With China, Brazil, India, Russia and other powerful emerging economies now at the table, is a new more multilateral era of governance emerging? This article examines the evidence. It details the governance reforms and new financing of the IMF but finds only very limited shifts in the engagement of major emerging economies - insufficient to position the IMF to address the global imbalances, to set new multilateral rules, to operate as an alternative to self-insurance, or indeed to provide a more multilateral response to the development emergency. The IMF is shifting between borrower dependence (relying on fee-paying borrowers for income); independence (with its own investment income); and lender-dependence (relying on wealthy members to extend credit lines to it). The result is an ambiguous set of forces restraining the IMF to stay as it is, and only weakly driving reform, creating a new order in which multilateral institutions - such as the IMF - may end up with only a limited role to play alongside emerging national and regional strategies, unless a more radical transformation begins.
Keywords: 330; Finanzkrise; Global Governance; Welt